CFD analysis on Ranque–Hilsch vortex tube with different cold orifice diameter and cold mass fraction. Issue 1 (31st December 2022) - Manickam, M.; Prabakaran, J.
Abstract : The vortex tube or Ranque–Hilsch vortex tube is a device that allows hot and cold air to be separated by the tangential flow of compressed air into the vortex chamber through the inlet nozzles and energy separation effects in a vortex tube have been investigated using a computational fluid dynamics model. The governing equations have been solved in an ANSYS Fluent code in a 3D compressible and turbulent model when Standard k-epsilon was used. The effects of geometrical parameters have been investigated. The results showed that the cold end diameter to tube diameter ratio (dc/D) affects the performance of the tube, and this effect changes when operating the tube at different cold mass fraction. The results showed that computational data were in good agreement with the experimental values.